Human Papillomavirus DNA in a Sample of Iraqi Women with Positive Visual Inspection by Acetic Acid - Halah Abdulwahhab Mohammed; Wasan Fawzi Sanad; Buthaina Ahmed Alwan (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: This study has conducted in Baghdad Teaching Hospital, Department of Obstetricsand Gyanecology, Al-Habebyia H. outpatient,Ibn-Albalady H. outpatient and 6 Primary Health CareCenters in Baghdad between June 2019 to March 2020.A Prospective and multicentric study.Aim of the Study: To asses the prevalence of HPV in a sample of Iraqi women.Patients and methods: The study include 268 married women between the age of 30 years old andmore, who were attending the outpatient department. Both screening tests; naked eye visual inspectionwith acetic acid &HPV test were performed.Results: The study included 268 women.The positivity rate of HPV for all women survived was 8.9%,19 % of women with positive VIA ,81% with negative VIA.All the positive VIA cases(19 %)and someofnegative VIA cases(18.6%) were randomly selected(because of their symptoms) underwentHPV test.After comparing the results of HPV test and VIA results, the sensitivity of VIA 95.8 %The specificity ofVIAwas 63.6%. Positive predictive values was 45.1%. Negative predictive values was 98%.Accuracyrate 71.3%.Conclusions:1. The prevalence of HPV infection among a sample of Iraqis women was very low.2. Estimation of HPV infection would provide valuable data particularly to introduce the strategies forthe screening of cervical cancer and HPV vaccination in Iraq.3.VIA with HPV DNA test may be a suitable substitute to Pap. smear as a screening tests for premalignantand malignant disease of the cervix.